Development of AC265347‐Inspired Calcium‐Sensing Receptor Ago‐Positive Allosteric Modulators. (29th July 2021) - Dinh, Le Vi; DeBono, Aaron; Keller, Andrew N.; Josephs, Tracy M.; Gregory, Karen J.; Leach, Katie; Capuano, Ben
Abstract: The calcium‐sensing receptor (CaSR) is a clinical target in the treatment of hyperparathyroidism and related diseases. However, clinical use of approved CaSR‐targeting drugs such as cinacalcet is limited due to adverse side effects including hypocalcaemia, nausea and vomiting, and in some instances, a lack of efficacy. The CaSR agonist and positive allosteric modulator (ago‐PAM), AC265347, is chemically distinct from clinically‐approved CaSR PAMs. AC265347 potently suppressed parathyroid hormone (PTH) release in rats with a lower propensity to cause hypocalcaemia compared to cinacalcet and may therefore offer benefits over current CaSR PAMs. Here we report a structure activity relationship (SAR) study seeking to optimise AC265347 as a drug candidate and disclose the discovery of AC265347‐like compounds with diverse pharmacology and improved physicochemical and drug‐like properties. Abstract : Positive cooperativity : The CaSR is a clinical target in the treatment of hyperparathyroidism and related diseases. AC265347 is an ago‐PAM chemically distinct from clinically approved CaSR PAMs. AC265347 potently suppressed PTH release in rats and is virtually devoid of hypocalcaemia and may therefore offer unique clinical benefits. Herein we report an SAR study disclosing AC265347‐like compounds with diverse pharmacology and improved physicochemical characteristics.